2013
DOI: 10.1038/aps.2013.56
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a human colorectal cancer cell line P6C with stem cell properties and resistance to chemotherapeutic drugs

Abstract: Aim:Cancer stem cells have the capacity to initiate and sustain tumor growth. In this study, we established a CD44+ colorectal cancer stem cell line with particular emphasis on its self-renewal capacity, enhanced tumor initiation and drug resistance.Methods:Fresh colon cancer and paired normal colon tissues were collected from 13 patients who had not received chemotherapy or radiotherapy prior to surgery. Among the 6 single-cell derived clones, only the P6C cell line was cultured for more than 20 passages in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 24 publications
0
35
0
2
Order By: Relevance
“…On day 10, spheroids with mean diameter of 100 mm were treated with 1, 5 or 10 mM of 5-FU (Sigma) [22] or the same concentration of 5-FU released from 5-FU-loaded PLGAcoated nanoparticles with or without the iron oxide core for 71 h. PLGA nanoparticles were used as a control for the drugloaded nanoparticles treatment. Before heat treatment, the medium was replaced with fresh RPMI 1640 culture medium.…”
Section: Cellular Uptake Of Nanoparticlesmentioning
confidence: 99%
“…On day 10, spheroids with mean diameter of 100 mm were treated with 1, 5 or 10 mM of 5-FU (Sigma) [22] or the same concentration of 5-FU released from 5-FU-loaded PLGAcoated nanoparticles with or without the iron oxide core for 71 h. PLGA nanoparticles were used as a control for the drugloaded nanoparticles treatment. Before heat treatment, the medium was replaced with fresh RPMI 1640 culture medium.…”
Section: Cellular Uptake Of Nanoparticlesmentioning
confidence: 99%
“…P6C is a CD44 hi primary CRC cell line of tumor-initiating potential (Supplementary Figure S1) [42]. Furthermore, CD44 + CD133 + cell population has been reported to enrich in colorectal tumor-initiating cells [43, 44].…”
Section: Resultsmentioning
confidence: 99%
“…Besides introduced markers listed in Table 1 Apart from in vitro studies, analyzing clinical samples revealed that CD44 could be used in combination with clinicopathological information to improve the OSCC prognosis, since its overexpression, in tumor samples and peripheral blood of OSCC patients, was correlated to poor prognosis LGR5 [152,153] EpCAM [120] BMI1 [119,218] CD24 [122,125] OCT4 [118,119] SOX2 [118,119,[149][150][151] NANOG [118,119] Colon and rectum CD44 [166,[180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198]200] CD133 [161-165, 171-178, 186-188, 232] ABCG2 [75,158,159] ALDH1 [198,[222][223][224]…”
Section: Oral Cavitymentioning
confidence: 99%
“…LGR5 has also been considered as a CRC-SC marker, because spheroid cultures derived from primary tumors were enriched for LGR5 expression [199,200], and LGR5 + cells form CRC cell lines displayed colony forming, tumorigenic [201], and therapy resistance [202] abilities. These reports are in agreement with other experiments indicating a significant decrease in survival [203], drug resistance [204], proliferation, migration, and tumorigenic abilities [205] of CRC cells upon LGR5 knockdown.…”
Section: Colon and Rectummentioning
confidence: 99%